POTENTIAL OF IKAITE TO RECORD THE EVOLUTION OF OCEANIC δ18O - Rickaby R.E.M.; Bennitt G.; Shaw S.; Kennedy H.; Zabel M.; Lennie A. (My University, 2006)
A challenge in the quest to understand the sensitivity of the climate system is the separation of the competing effects of ice volume or sea level, salinity, and temperature on foraminiferal δ18O. We present precipitation experiments on the mineral ikaite, a hydrated form of calcium carbonate found in organic carbon-rich deep-marine sediments, that show that the hydration waters within the ikaite crystal capture the δ18O of seawater (δ18 Osw) with a fractionation factor of 1.0029 (±0.0002). The δ18Osw measures the volume of continental ice, with an overprint of local salinity. Isolation of δ18Osw by analysis of the hydration waters of sedimentary ikaite preserved at temperatures <4 °C could be exploited to create a record of sea level during the pleistocene. preliminary data δ18Osw from hydration waters of ikaite at the Last Glacial Maximum agree with estimates from modeling of pore waters that Antarctic Bottom Water was +1.4‰ ± 0.2‰ heavier.
Keywords: CLIMATE; ICE VOLUME; IKAITE; OXYGEN ISOTOPES; PLEISTOCENE; SEA LEVEL; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен